Short Film About The Dangers of Online Loans for Young Adults in Surabaya - Katya Jocelyn (Institut Seni Indonesia Padangpanjang, 2024)
Advances in technology conveniences society to use online transactions as daily lifestyle. One of the services in financial technology advances is online loan service, lending users temporary funds that is needed. Social groups in society that have expertise in utilizing technology and have a hedonistic lifestyle are dominated by young adults. Enjoying life became their main purpose, driving young adults to use online loans without thinking twice. Social media also triggers young adults to feel FOMO (Fear Of Missing Out), so they use the services to fulfill their desires. Online loans become a financial stumbling block if users do not have financial literacy. This caused many young adults fall into debts, unable to settle the bills with interest. Feeling that there is no way out, users who are trapped in debt will try to find a quick solution, hoping to solve the problem by using other loan services. In the end, this action did not completely solve the problem. The psychological pressure experienced by young adults often led them to do extreme things, such as taking their own life or someone else's. A short film about the dangers of online loans with the title